How platform leadership stimulates innovative behavior in frontline nurses: a cross-level moderated mediation model - Ning Li; He Wang (Scientific Reports)
Abstract Platform leadership emphasizes shared goals, unlocking potential, and generating positive impacts for both leaders and subordinates. This style greatly influences frontline nurses’ attitudes and behaviors, underscoring the need to study how it stimulates innovation. Using 422 questionnaires from 52 hospitals, internal mechanisms of platform leadership and frontline nurses’ innovation were analysed with Mplus 8.0 and HLM 6.08. The study uncovered the following results: Firstly, platform leadership was positively correlated with frontline nurses’ innovative behavior. Secondly, leader–member exchange (LMX) and relational energy served as mediators between platform leadership and frontline nurses’ innovative behavior. Thirdly, the error management climate was positively correlated with frontline nurses’ innovative behavior and acted as a moderator in the relationship between platform leadership and frontline nurses’ innovative behavior. The study’s findings reveal the internal mechanisms of platform leadership and frontline nurses’ innovative behavior, offering valuable insights for organizational improvement.